Da fabrikkerne lukkede: Den amerikanske afindustrialiseringsfilm - Jensen, Mikkel (Passage - Tidsskrift for litteratur og kritik, 2020)
This article presents readings of three American films that engage with American histories of deindustrialization: Gung Ho, Roger & Me and 8 Mile. Since the publication of Barry Bluestone and Bennett Harrison’s The Deindustrialization of America in 1982, much research has explored important economic and social-historical aspects concerning the waning number of industrial jobs in the U.S. and the impact of factory closings on many cities in the so-called Rust Belt. This paper explores a cultural side of that story, especially taking its cue from Sherry Lee Linkon’s The Half-Life of Deindustrialization (2018). The paper explores how Gung Ho’s comedic depiction of deindustrialization all but elides important class tensions, how Roger & Me, among other things, intervenes in discussions regarding priorities in leftist discourse in the U.S. and how 8 Mile explores a tension between industrial and creative work in the 1990s in Detroit. It closes by pointing to the relevance of further research into the cultural aspects of deindustrialization.